STUDI FENOMENOLOGI TERHADAP PELECEHAN SEKSUAL SESAMA JENIS DI KAMPUS: REALITAS DAN PENGALAMAN LAKI-LAKI SEBAGAI KORBAN - Injany, Evinsa; Hakim, Atikah Kanza Atsarina; Lutfiputri, Nadia Farah; Mahmud, Zaki Khudzaifi; Hindarto, Isni Hindriaty (Interaksi: Jurnal Ilmu Komunikasi, 2024)
Research on sexual harassment has gotten a lot of attention in the last three decades, partly because the victims are not solemnly women and children, men also have a chance to become one. Sexual harassment might occur in any setting, anywhere, at any moment, including at higher education institutions. The aim of this study is to examine how males interpret the experience of sexual harassment by same-sex perpetrators. This study further explores the understanding of experiences, and responses of five male students who encountered sexual harassment in a higher education setting, using qualitative methodology, a phenomenological approach, and data collection techniques in the form of interviews. The results of data collection indicate that the acts of sexual harassment experienced by the informants can be divided into direct (physical contact) or indirect. Then there is a connection between how males perceive their sexual harassment experience and the concept of masculinity. Furthermore, victims of samesex sexual harassment's reactions and interpretations of sexual harassment are influenced by their own experiences and self-perceptions.